Land-use implications of energy transition pathways towards decarbonisation – Comparing the footprints of Vietnam, New Zealand and Finland. (July 2022) - Tran, Thuc Han; Egermann, Markus
Abstract: Conceptual and empirical work on socio-technical transitions, such as energy transition strategies, often disregard the limited planetary capacity of available land. This paper explores the trade-offs between energy transition pathways and land use in different geographical contexts. We draw on empirical data from three contrasting case-study countries: Vietnam, New Zealand and Finland. An enhanced calculation model based on the Ecological Footprint method is used to assess land consumption for different transition pathways towards a low-carbon society. More specifically, the spatial impacts of the energy sector and its carbon dioxide emissions are assessed for different timeframes, namely the past, the present and future scenarios (by 2030 and the 2040s) based on the national energy strategies of these countries. The results show a lack of consideration in these strategies of the land area required to ensure an adequate implementation for each national territory. Hence, we argue for an acknowledgement of spatial factors, namely land availability and the geographical context, in theories and policy strategies on socio-technical transitions. Highlights: Investigates implications of energy strategies in different geographical contexts. Modifies Ecological Footprint model to provide a more robust planning tool. Compares energy footprint of three contrasting countries over different time horizons. Challenges of emerging countries to meet the future demands within available land. Integrates spatial aspects as a holistic measure into energy and climate policy.